Assessing local conservation priorities of useful woody species within agroforestry systems along Ouémé catchment in Benin (West Africa) - Lokonon, Bruno Enagnon; Mangamana, Essomanda Tchandao; Kakaï, Romain Glèlè; Sinsin, Brice (Ethnobiology and Conservation, 2017)
Ouémé catchment experiences increasing degradation of its natural resources due to anthropogenic pressure. Consequently, most of the agroforestry species as well as the cultural and Indigenous knowledge related to them are facing a very high risk of extinction. The present research aimed to assess the biodiversity of the useful woody species in this area and their cultural importance and then prioritize these woody species for conservation purpose. An ethnobotanical survey was carried out among 411 randomly selected households followed by an ecological survey conducted in 69 random plots of 0.15 ha. Ecological and ethnobotanical parameters were calculated and then analyzed. To determine the local priorities species for conservation, a local conservation priority index (LCPI) was computed for each species. The high value of LCPI for a given species indicates the need for a greater level of attention for conservation and management. Forty-five useful woody species belonging to 21 families dominated by Leguminosae (24.44%) and Anacardiaceae (8.88%) were reported. The forty-five species were categorized in six use categories by the informants: food, medicinal, construction, fuel, veterinary and technology. The most useful species were Elaeis guineensis (UV=0.24), followed by Parkia biglobosa (UV=0.19) and Vitellaria paradoxa (UV=0.18). The prioritization method yielded top ten ranked species: Adansonia digitata, Parkia biglobosa, Pterocarpus erinaceus, Irvingia gabonensis, Milicia excelsa, Tamarindus indica, Vitex doniana, Prosopis africana, Diospyros mespiliformis and Pterocarpus santalinoides. With the aim of establishing the sustainable management in the catchment, we suggest that more attention be paid to the aforementioned species as part of rehabilitation activities.